Mercado financeiro na Classificação Decimal de Dewey: proposta de expansão - Gil, Luana Carolina de Castro (Universidade Federal de São Carlos, 2022)
Bibliographic classification systems play a very important role in organizing works in the collection, as well as retrieving information from databases. Considering that obtaining privileged information in the context of the financial market provides a competitive advantage, the question is whether Class 332 dedicated to Financial Economics covers the financial market subject in its scope and detail? Therefore, the general objective of this research is to put the expansion of the representation of the financial market in the Dewey Decimal Classification (DDC). This is an exploratory and descriptive study, which has an applied nature and a qualitative approach. Therefore, a bibliographic research was carried out to analyze the literature on the subject, as well as to identify the terms used in the financial market. Furthermore, it was based on the methodology of Barité Roqueta (1990) to develop the proposal to modify the classification scheme. As a result, it is possible to insert about fifty terms, which were organized by expanding six existing subclasses and creating seven other subclasses. It is concluded that the proposal can contribute to the organization of knowledge about the financial market, as well as meet the informational needs of users.
Financial market in the Decimal Classification of Dewey: expansion proposal
Keywords: Mercado financeiro; Sistemas de classificação; Classificação Decimal de Dewey; Proposta de expansão; Financial market; Classification systems; Dewey Decimal Classification; Expansion proposal; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA